A room temperature high-sensitivity reversible gas-sensitive material, a preparation method thereof and application thereof in an ammonia gas sensor
Patent Information
- Application Number
- CN202611146336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]然而,纯PANI传感器仍存在响应恢复慢(质子转移和链构象变化需较长时间)、选择性不足(易受其他碱性气体或极性分子干扰)、长期稳定性差(小分子掺杂剂易流失、PANI链易氧化)以及溶液加工性差(刚性主链难分散、成膜质量低)
[0023]1、本发明采用大分子磷钨酸(HPW,Keggin型杂多酸)替代传统小分子酸作为聚苯胺(PANI)的掺杂剂,利用HPW的大尺寸和空间位阻效应,在聚合过程中撑开PANI链段,可暴露更多NH3吸附活性位点,诱导多级孔结构,并促进PANI链定向排列,提高结晶区比例,从而加速响应恢复并增强吸附能力。同时,HPW与PANI间形成强静电作用,可抑制掺杂剂流失,提高长期稳定性;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas sensor technology, specifically relating to room temperature high-sensitivity reversible gas-sensitive materials, their preparation methods, and their application in ammonia sensors. Background Technology
[0002] Ammonia (NH3) sensors have important applications in environmental monitoring, food safety, agriculture, and medical diagnosis. Existing sensors mainly fall into three categories: optical, electrochemical, and chemielectric resistive. Among these, chemielectric resistive sensors have become the mainstream technology due to their simple structure, low power consumption, and ease of integration.
[0003] The conductive polymer polyaniline (PANI) has attracted much attention in NH3 sensing due to its room-temperature operating capability, good flexibility, and reversible doping / dedoping properties. PANI's response to NH3 is based on proton transfer: NH3, as a Lewis base, removes protons from the PANI chain, transforming it from a conductive emerald green imine salt (ES) to an insulating emerald green imine base (EB), resulting in a significant increase in resistance; after the NH3 is removed, PANI can be reprotonated to restore its conductive state.
[0004] However, pure PANI sensors still suffer from slow response recovery (proton transfer and chain conformation changes require a long time), insufficient selectivity (susceptible to interference from other alkaline gases or polar molecules), poor long-term stability (small molecule dopants are easily lost, and PANI chains are easily oxidized), and poor solution processability (rigid backbones are difficult to disperse, resulting in low film quality). To address these challenges, researchers have attempted strategies such as constructing porous structures, introducing highly conductive carbon materials, morphology control, or interface engineering. However, most of these efforts focus on introducing a second phase, and systematic research on the structural control of intrinsic PANI doped states (such as the molecular size and binding mode of dopants and their impact on chain stacking) is still lacking.
[0005] Therefore, developing a room-temperature high-sensitivity reversible gas-sensitive material and its preparation method is essential for the application of ammonia sensors. Summary of the Invention
[0006] The purpose of this invention is to provide a room-temperature, highly sensitive, and reversible phosphotungstic acid / polyaniline / graphene oxide composite material and its preparation method. This invention also provides the application of this composite material in an ammonia sensor and further discloses the preparation method of the ammonia sensor. This invention uses macromolecular phosphotungstic acid (HPW, a Keggin-type heteropoly acid) instead of traditional small-molecule acids as a dopant. The large size of HPW can expand the PANI chain segments, exposing more active sites, inducing a hierarchical porous structure, and promoting the directional alignment of PANI chains, increasing the proportion of crystalline regions, thereby accelerating response recovery and enhancing adsorption capacity. Simultaneously, the strong electrostatic interaction between HPW and PANI can inhibit dopant loss and improve stability. Furthermore, to overcome the defects of HPW's tendency to aggregate and potentially increase inter-chain charge barriers, this invention further introduces carbon materials such as graphene oxide (GO) to construct a three-dimensional structure through π-π interactions and hydrogen bond networks, synergistically improving conductivity and structural uniformity.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0008] A room-temperature highly sensitive reversible gas-sensitive material is prepared by in-situ oxidative polymerization of macromolecular heteropolyacids, aniline, carbon materials and initiators, wherein the macromolecular heteropolyacids are Keggin-type or Dawson-type heteropolyacids.
[0009] Preferably, the Keggin-type heteropolyacid is phosphotungstic acid (H3PW). 12 O 40 ), silicotungstic acid (H4SiW) 12 O 40 ), phosphomolybdic acid (H3PMo) 12 O 40 ), molybdenum silicate (H4SiMo) 12 O 40 ) and phosphotungstic acid (H3PW) X Mo 12-X O 40 The carbon material is one or more of the following: graphene oxide, functionalized graphene oxide, reduced graphene oxide (rGO), graphene nanosheets, carbon nanotubes, carbon nanofibers, MXene, carbon black, and carbon quantum dots; the initiator is one or more of the following: ammonium persulfate, potassium persulfate, hydrogen peroxide, ferric chloride, and copper chloride; more preferably, the functionalized graphene oxide is one or more of the following: carboxylated GO, aminated GO, and sulfonated GO.
[0010] Preferably, the heteropoly acid is phosphotungstic acid; the carbon material is graphene oxide; and the initiator is ammonium persulfate.
[0011] Preferably, the mass ratio of the macromolecular heteropolyacid, aniline monomer, and carbon material is (5-3000):100:(0-1000); that is, based on aniline monomer, the heteropolyacid doping can achieve different degrees of doping from 5% to 3000%, and the carbon material doping ranges from 0% to 1000%, wherein the carbon material is not zero; the molar ratio of the initiator to the aniline monomer is 0.25:1 to 3:1.
[0012] This invention also discloses a method for preparing the room-temperature high-sensitivity reversible gas-sensitive material, comprising the following steps:
[0013] S1. Prepare an aqueous dispersion of carbon material and an aniline ethanol solution respectively. Mix the aniline ethanol solution and the aqueous dispersion of carbon material under ice bath conditions for 25-35 minutes.
[0014] S2. Add an aqueous solution containing macromolecular heteropolyacid to the mixture prepared in S1, adjust the pH of the system to 3-4, and continue mixing in an ice bath for 25-35 minutes.
[0015] S3. Under ice bath conditions, add the initiator to the mixture obtained in S2 and stir the system. After the reaction lasts for 10-14 hours, the resulting product is purified and dried to obtain the powdered target product, which is the room temperature high-sensitivity reversible gas-sensitive material.
[0016] Preferably, in S1, the mass concentration of the aqueous dispersion containing carbon materials is 2 mg / mL; the preparation method is as follows: take an appropriate amount of graphene oxide (GO) aqueous solution (the concentration of the GO aqueous solution is 10 mg / mL, commercially available), add deionized water to dilute to 2 mg / mL, and ultrasonically disperse in an ice bath for 2 hours; the concentration of the aniline ethanol solution is 0.5 mmol / mL, which is prepared by dissolving aniline monomer in anhydrous ethanol and ultrasonically mixing; the reason for using an ice bath in this invention is to inhibit the aggregation between GO sheets, thereby obtaining a stable and uniform dispersion; the concentration of the aqueous solution containing macromolecular heteropolyacids in S2 is 0.1 mmol / mL;
[0017] Preferably, in step S3, the purification and drying operations are as follows: the product after reaction is washed at least three times by centrifugation with deionized water and anhydrous ethanol, and the resulting precipitate is then freeze-dried; wherein, the washing solvent used during washing can be water, ethanol, methanol, acetone or a mixture thereof.
[0018] The present invention also discloses the application of the room temperature high-sensitivity reversible gas-sensitive material in an ammonia sensor.
[0019] This invention further discloses a method for preparing a room-temperature high-sensitivity reversible ammonia sensor, comprising the following steps:
[0020] S1. Weigh an appropriate amount of the room temperature high-sensitivity reversible gas-sensitive material powder, add isopropanol, and grind it into a uniform paste.
[0021] S2. A paste-like material is coated onto the surface of a substrate with gold electrodes. After natural drying, a gas-sensitive thin film is formed, which is then soldered to the four corner bases to obtain the sensor device. In this invention, the substrate can be any of ceramic, silicon wafer, flexible polymer (PET, PI), glass, etc. The electrode preparation coating method can be spin coating, drop coating, spray coating, screen printing, or inkjet printing.
[0022] Compared with the prior art, the present invention has the following technical effects:
[0023] 1. This invention uses macromolecular phosphotungstic acid (HPW, a Keggin-type heteropolyacid) to replace traditional small-molecule acids as a dopant for polyaniline (PANI). Utilizing the large size and steric hindrance effect of HPW, it expands the PANI chain segments during polymerization, exposing more NH3 adsorption active sites, inducing a hierarchical porous structure, and promoting the directional alignment of PANI chains, increasing the proportion of crystalline regions, thereby accelerating response recovery and enhancing adsorption capacity. Simultaneously, a strong electrostatic interaction forms between HPW and PANI, which can inhibit dopant loss and improve long-term stability.
[0024] 2. In the system of this invention, GO and HPW compete for the adsorption of aniline monomers. By adjusting the amount of GO, the product can be transformed from being mainly composed of ammonium phosphotungstate crystals to being mainly composed of PANI / GO intercalation composites. An appropriate amount of GO (8 mg) forms a composite crystal with an ammonium phosphotungstate core and PANI / GO shell, exhibiting a rhombic dodecahedral morphology. This structure has distinct edges and corners and micro-protrusions on the surface, which is beneficial for gas adsorption and diffusion; it also has a high specific surface area, hierarchical pores, and a good conductive network.
[0025] 3. The preparation process is simple. In this invention, aniline, HPW, GO and initiator (KPS) are polymerized in situ in a weakly acidic aqueous solution in one step, which simultaneously realizes the formation of ammonium phosphotungstate crystals, the polymerization of aniline on GO sheets, and the layer-by-layer self-assembly under electrostatic action, and finally forms a morphology with ammonium phosphotungstate as the core and PANI / GO as the shell.
[0026] 4. The HPG8 sensor manufactured in this invention has high sensitivity to NH3 at room temperature, fast response recovery, complete recovery, excellent selectivity to common interfering gases, and long-term stability.
[0027] This invention introduces carbon materials such as graphene oxide (GO) to construct a three-dimensional structure through π-π interactions and hydrogen bond networks, synergistically improving conductivity and structural uniformity, overcoming the problems of easy aggregation and potential increase in inter-chain charge barriers caused by high-performance carbon dioxide (HPW). Furthermore, this invention is the first to apply this system to room-temperature NH3 detection and optimizes the GO content. Experiments show that the obtained sensor exhibits good linear response in the 0.2–50 ppm NH3 concentration range, with a response value reaching 180% (R0) for 20 ppm NH3. g -R a ) / R a Its response / recovery time (54 s / 264 s) is superior to most pure PANI sensors, and it can fully recover within 10 min. It also has extremely low response to common interfering gases (ethanol, acetone, etc.), exhibiting high sensitivity, fast response, complete recovery, excellent selectivity and long-term stability. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the structure of the gas sensor element of the present invention;
[0029] Figure 2 This is a schematic diagram of the structure of the gas sensor of the present invention;
[0030] Figure 3 XRD patterns of HPW-PANI / GO samples with different graphene contents;
[0031] Figure 4 These are scanning electron microscope images of HPW-PANI / GO with different graphene contents; (a) HP sample (GO=0 mg); (b) HPG4 sample (GO=4 mg); (c) HPG8 sample (GO=8 mg); (d) HPG12 sample (GO=12 mg).
[0032] Figure 5 These are (a) a cross-sectional view and (b) an elemental distribution diagram of the HPG8 sample;
[0033] Figure 6 This is a transmission electron microscope (TEM) image of HPG8;
[0034] Figure 7 These are nitrogen adsorption-desorption curves and corresponding pore size distribution diagrams;
[0035] Figure 8 These are the resistance change curves under different ammonia concentrations (0.2-50 ppm);
[0036] Figure 9 This involves testing the response recovery time of HPW-PANI / GO sensors with different graphene contents;
[0037] Figure 10It is a selective test of the HPG8 sensor;
[0038] Figure 11 These are the results of long-term stability tests on the HPG8 sensor. Detailed Implementation
[0039] The present invention will be further described below with reference to specific embodiments.
[0040] Example 1
[0041] This embodiment presents a room-temperature highly sensitive reversible gas-sensitive material, prepared by in-situ oxidative polymerization of a macromolecular heteropolyacid phosphotungstic acid, aniline monomer, initiator, and graphene oxide. The ratio of the macromolecular heteropolyacid, polyaniline, and carbon material is 2500:100:8.
[0042] Its preparation method includes the following steps:
[0043] S1. Prepare an aqueous dispersion of graphene oxide and an aniline ethanol solution respectively. Mix the aniline ethanol solution and the aqueous dispersion of carbon material in an ice bath for 30 min. The preparation method of the aqueous dispersion of graphene oxide in this embodiment is as follows: Take 0.8 mL of graphene oxide (GO) aqueous solution (the concentration of the GO aqueous solution is 10 mg / mL, commercially available), add deionized water to dilute to 2 mg / mL, and ultrasonically disperse in an ice bath for 2 hours. The aniline ethanol solution is obtained by dissolving aniline monomer in anhydrous ethanol and ultrasonically mixing. The purpose of using an ice bath in this invention is to inhibit the aggregation between GO sheets, thereby obtaining a stable and uniform dispersion. In this embodiment, the concentration of the aniline ethanol solution is 0.5 mmol / mL.
[0044] S2. Add a 0.1 mmol / mL phosphotungstic acid aqueous solution to the mixture in S1, adjust the pH of the system to 3-4, and continue mixing in an ice bath for 30 min.
[0045] S3. Under ice bath conditions, potassium persulfate, the initiator, is added to the mixture obtained in S2, and the system is stirred. After reacting for 12 hours, the resulting product is purified and dried to obtain a powdered target product, which is the room-temperature highly sensitive reversible gas-sensitive material. The molar ratio of the initiator to the aniline monomer is 1:1. The specific purification and drying procedures are as follows: the product after reaction is washed three times by centrifugation with deionized water and anhydrous ethanol, respectively, and the resulting precipitate is then freeze-dried.
[0046] Example 2
[0047] The room-temperature high-sensitivity reversible gas-sensitive material and its preparation method in this embodiment are the same as in Example 1, except that the amount of GO aqueous solution measured in S1 is 0.4 mL, that is, the ratio of the amount of macromolecular heteropolyacid, aniline monomer and carbon material is 2500:100:4.
[0048] Example 3
[0049] The room-temperature high-sensitivity reversible gas-sensitive material and its preparation method in this embodiment are the same as in Example 1, except that the amount of GO aqueous solution measured in S1 is 1.2 mL, that is, the ratio of the amount of macromolecular heteropolyacid, polyaniline and carbon material is 2500:100:12.
[0050] Comparative Example 1
[0051] The room-temperature high-sensitivity reversible gas-sensitive material and its preparation method in this embodiment are the same as in Example 1, except that GO aqueous solution is no longer added in S1.
[0052] In other embodiments of the present invention, the combination of phosphotungstic acid (HPW) and graphene oxide (GO) is not limited to the present invention. Other macromolecular heteropolyacids or superacids with similar molecular size, steric hindrance effect, and strong proton acidity can also be used as dopants and morphology modifiers for polyaniline to achieve similar technical effects. The macromolecular acid may be, but is not limited to, silicotungstic acid (H4SiW). 12 O 40 ), phosphomolybdic acid (H3PMo) 12 O 40 ), molybdenum silicate (H4SiMo) 12 O 40 ), phosphotungstic molybdenum acid (H3PW) X Mo 12-X O 40 Keggin-type or Dawson-type heteropolyacids, etc.
[0053] In other embodiments, the graphene oxide (GO) used in this invention can also be replaced by other two-dimensional or one-dimensional carbon nanomaterials rich in surface functional groups, with high specific surface area and good conductivity, to achieve similar composite structure regulation and performance improvement. The replacement materials are functionalized graphene oxide (such as carboxylated, aminated, or sulfonated GO), reduced graphene oxide (rGO), graphene nanosheets, carbon nanotubes (CNTs, including single-walled, multi-walled, and functionalized CNTs), carbon nanofibers, and MXene (such as Ti3C2T). X Nb2CT X (Transition metal carbon / nitrides, etc.). These materials can form hydrogen bond networks or π-π interactions with heteropolyacids and polyaniline, guiding the formation of ordered intercalation structures and synergistically improving gas-sensing performance.
[0054] Example 4 Application
[0055] This embodiment uses the room-temperature high-sensitivity reversible gas-sensitive material powder prepared in Example 1 as an example to fabricate a room-temperature high-sensitivity reversible ammonia gas sensor. The preparation method includes the following steps:
[0056] S1. Weigh 50 mg of the room temperature high-sensitivity reversible gas-sensitive material powder, add 100 μL of isopropanol, and grind into a uniform paste.
[0057] S2. Using a dropper, evenly coat the paste-like material onto the surface of a ceramic substrate with gold electrodes. After air drying, a gas-sensitive thin film is formed, resulting in a gas sensor element, such as... Figure 1 As shown, the gas sensor element is then welded to the four corner bases to obtain the sensor device. Figure 2 As shown. In the preparation process, the four corner bases, electrode substrates, and other components can all be commercially available. It is only necessary to place the gas-sensitive material prepared in this invention on the surface of the electrode substrate, which greatly facilitates the preparation of ammonia sensors.
[0058] To further illustrate the effects of this invention, different samples HP, HPG4, HPG8, and HPG12 (corresponding to Example 1, Example 2, Example 1, and Example 3, respectively) were prepared by varying the amount of graphene oxide added. The resulting HPW-PANI / GO samples were then subjected to performance tests including XRD, SEM, TEM, and elemental analysis. Specific test results are shown in [link to specific test results]. Figure 3-11 .
[0059] Table 1 Test Items, Instruments and Standards
[0060] .
[0061] Figure 3 These are XRD patterns of HPW-PANI / GO samples with different graphene contents. Figure 3 The XRD pattern shows that, without the addition of GO, all peaks in the HP sample correspond to PDF card PDF#50-0305 (standard crystal card for ammonium phosphotungstate), which corresponds to the cubic crystal system of ammonium phosphotungstate ((NH4)3PW). 12 O 40 ·9.5H2O). Samples with 4 mg and 8 mg GO added not only showed peaks of ammonium phosphotungstate, but also new XRD diffraction peaks around 8.2°, corresponding to the characteristic diffraction peaks of GO, but significantly shifted to lower peak positions (the standard diffraction peak of GO is around 11.3°), proving that phosphotungstic acid / PANI chains intercalated between GO layers, increasing the interlayer spacing. The sample with 12 mg GO added had only 3 distinct peaks, among which the broad peaks at 18.6° and 28.9° belonged to the PANI chain. These results indicate that when the GO content is low, HPW dominates, forming a large amount of ammonium phosphotungstate crystals. When the GO content is high, almost all aniline cations are captured by the GO surface, and HPW loses its ammonium source for crystal formation (NH4 provided by aniline). +It can only be dispersed in the PANI / GO matrix in molecular or ionic state, and mainly plays a doping role.
[0062] Figure 4 These are scanning electron microscope (SEM) images of HPW-PANI / GO with different graphene contents, from... Figure 4 As can be seen, the HP sample without added GO exhibits approximately spherical particles with numerous fine protrusions on the surface, and the particle size is approximately 50 nm. When the GO addition is 4 mg, the sample morphology evolves into a near-cubic structure, with the particle size increasing to approximately 200 nm, and the surface becoming relatively smooth. Further increasing GO to 8 mg, the sample exhibits a typical regular rhombic dodecahedral structure with sharp edges and a smooth surface but with distributed micro-protrusions, and the particle size distribution is uneven (tens to hundreds of nm). When the GO addition reaches 12 mg, the sample transforms into a distinct lamellar structure, with polyaniline (PANI) uniformly growing on the GO lamellar surface, forming a bulging protrusion morphology. SEM results demonstrate the crucial role of GO in regulating the crystal growth, aggregate structure, and morphology of the composite material.
[0063] Figure 5 These are (a) a cross-sectional view and (b) an elemental distribution diagram of the HPG8 sample. The cross-sectional view shows that the HPG8 sample has a loose internal structure, with C, N, O, P, and W elements evenly distributed. This indicates that PANI, GO, and HPW form a three-dimensional interpenetrating network structure. The loose structure provides a rapid channel for gas diffusion, and the uniform elemental distribution ensures the continuity of charge transfer paths and the uniform exposure of active sites.
[0064] Figure 6 This is a transmission electron microscope image of HPG8. The image shows that ammonium phosphotungstate serves as the core, and PANI grows uniformly on the GO sheets and gradually encapsulates the ammonium phosphotungstate core, eventually forming a large-sized regular rhombic dodecahedral structure.
[0065] Figure 7 These are nitrogen adsorption-desorption curves and corresponding pore size distribution diagrams. (a) HP; (b) HPG4; (c) HPG8; (d) HPG12; From Figure 7 As can be seen, different GO contents have a significant regulatory effect on the specific surface area and pore structure of the composite material. The specific surface area of the HP sample without added GO is only 8.7 m². 2 The pore size distribution is concentrated around 36.4 nm and extends to larger sizes, indicating that the material has a predominantly macroporous structure, possibly originating from interstitial pores formed by particle packing. After introducing 4 mg of GO (HPG4), the specific surface area increased to 19.5 m² / g. 2 The pore size distribution tends to be concentrated, with a diameter of approximately 8.7 nm, exhibiting mesoporous characteristics. When the GO content increases to 8 mg (HPG8), the specific surface area reaches its maximum value of 46.5 m².2 The specific surface area was significantly higher than that of similar materials reported in the literature; its pore size distribution showed a sharp micropore peak at 2.1 nm and a strong mesopore peak at 8-9 nm. Further increasing GO to 12 mg (HPG12) resulted in a decrease in specific surface area to 31.2 m². 2 / g, with pore size concentrated around 8.3 nm, mainly mesoporous.
[0066] The HPG8 sample exhibits the highest specific surface area and a unique pore structure. The 2.1 nm micropores likely originate from the regular intercalation structure formed between the PANI chains and the GO layer, while the 8-9 nm mesopores arise from particle packing or shell pores. This hierarchical pore structure provides abundant adsorption sites and rapid diffusion channels for NH3 gas molecules. Simultaneously, the high specific surface area enhances gas-solid interface reactions, forming a crucial structural basis for the HPG8 sensor's high sensitivity and rapid response.
[0067] Figure 8 These are resistance change curves at different ammonia concentrations (0.2-50 ppm). (a) HP; (b) HPG4; (c) HPG8; (d) HPG12; The real-time resistance response of HP, HPG4, HPG8, and HPG12 sensors to different concentrations of NH3 was mainly tested at room temperature. The resistance of all samples increased monotonically with increasing NH3 concentration, exhibiting typical p-type semiconductor behavior. Among them, the resistance of the HP sensor could not be fully recovered after the removal of NH3, and the curve continued to drift upward, indicating its poor reversibility. The resistance changes of HPG4 and HPG8 were significantly greater than those of HP and HPG12, especially HPG8. Specifically, the initial resistance of HPG4 (1.87 MΩ) and HPG8 (0.86 MΩ) was significantly lower than that of HP (8.89 MΩ) and HPG12 (3.62 MΩ), indicating that they formed a more complete conductive network.
[0068] Figure 9This study tested the response recovery time of HPW-PANI / GO sensors with different graphene contents. The response recovery performance of HPG4, HPG8, and HPG12 sensors to 20 ppm NH3 was tested at room temperature. The response values were 140%, 180%, and 119%, respectively, with response times of 45 s, 54 s, and 90 s, and recovery times of 221 s, 264 s, and 462 s, respectively. Reliable data could not be obtained for the HP sample due to baseline drift. Furthermore, HPG4 and HPG8 completely recovered to the initial baseline within 10 minutes after NH3 removal (100% recovery rate), while HPG12 failed to fully recover within the same time, exhibiting significant residual resistance. This is because HPG8 has a high specific surface area and numerous micropores and mesopores. The micropores provide strong adsorption sites, contributing to the high response, but NH3 desorption from the micropores requires a longer time, although complete desorption still occurs within 10 minutes. HPG4 has a lower specific surface area and a simpler pore structure (mesoporous), resulting in weaker but completely reversible adsorption. HPG12 is mainly composed of stacked layers. Although its specific surface area is higher than that of HPG4, its pores are irregular. Furthermore, the PANI capping layer may form irreversible chemisorption sites, making it difficult for some products to desorb after NH3 adsorption, and thus it cannot be fully recovered in a short period of time.
[0069] Figure 10 This is a selectivity test of the HPG8 sensor. The sensor's response to 50 ppm NH3, trimethylamine (TMA), triethylamine (TEA), methane (CH4), ethanol (EtOH), acetone (Ace), ethyl acetate (EA), H2S, H2, CO, and NO2 was tested at room temperature. The HPG8's response to NH3 (380%) was significantly higher than all other gases. Its responses to TMA and TEA were only about 1 / 4 and 1 / 6 of those to NH3, respectively. The responses to oxygenated organic compounds, methane, and inorganic gases were all below 0.1, demonstrating excellent selectivity.
[0070] Figure 11 These are the long-term stability test results for the HPG8 sensor. The test measured the stability of the HPG8 over 13 weeks, and the response value remained essentially unchanged.
Claims
1. A room-temperature high-sensitivity reversible gas-sensitive material, characterized in that, It is prepared by in-situ oxidative polymerization reaction of macromolecular heteropolyacid, aniline, carbon material and initiator, wherein the macromolecular heteropolyacid is a Keggin type or Dawson type heteropolyacid.
2. The room-temperature high-sensitivity reversible gas-sensitive material according to claim 1, characterized in that, The Keggin-type heteropolyacid is phosphotungstic acid (H3PW). 12 O 40 ), silicotungstic acid (H4SiW) 12 O 40 ), phosphomolybdic acid (H3PMo) 12 O 40 ), molybdenum silicate (H4SiMo) 12 O 40 ) and phosphotungstic acid (H3PW) X Mo 12-X O 40 The carbon material is one or a mixture of two or more of the following: graphene oxide, functionalized graphene oxide, reduced graphene oxide (rGO), graphene nanosheets, carbon nanotubes, carbon nanofibers, MXene, carbon black, and carbon quantum dots; the initiator is one or a mixture of two or more of the following: ammonium persulfate, potassium persulfate, hydrogen peroxide, ferric chloride, and copper chloride.
3. The room-temperature high-sensitivity reversible gas-sensitive material according to claim 2, characterized in that, The Keggin-type heteropolyacid is phosphotungstic acid; the carbon material is graphene oxide; and the initiator is ammonium persulfate.
4. The room-temperature highly sensitive reversible gas-sensitive material according to any one of claims 1, characterized in that, The mass ratio of the macromolecular heteropolyacid, aniline monomer, and carbon material is (5-3000):100:(0-1000), and the molar ratio of the initiator to the aniline monomer is 0.25:1 to 3:
1.
5. The method for preparing the room-temperature highly sensitive reversible gas-sensitive material according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Prepare an aqueous dispersion of carbon material and an aniline ethanol solution respectively. Mix the aniline ethanol solution and the aqueous dispersion of carbon material under ice bath conditions for 25-35 minutes. S2. Add an aqueous solution containing macromolecular heteropolyacids to the S1 mixture and adjust the pH of the system to 3-4. Continue mixing in an ice bath for 25-35 minutes. S3. Under ice bath conditions, add the initiator to the mixture obtained in S2 and stir the system. After the reaction lasts for 10-14 hours, the resulting product is purified and dried to obtain the powdered target product, which is the room temperature high-sensitivity reversible gas-sensitive material.
6. The method for preparing a room-temperature highly sensitive reversible gas-sensitive material according to claim 5, characterized in that, In S1, the mass concentration of the aqueous dispersion containing carbon material is 2 mg / mL; the concentration of the aniline ethanol solution is 0.5 mmol / mL; and the concentration of the aqueous solution containing macromolecular heteropolyacid in S2 is 0.1 mmol / mL.
7. The method for preparing a room-temperature highly sensitive reversible gas-sensitive material according to claim 5, characterized in that, In S3, the specific purification and drying operations are as follows: the product after reaction is washed at least 3 times by centrifugation with deionized water and anhydrous ethanol, and the resulting precipitate is then freeze-dried.
8. The application of the room temperature high-sensitivity reversible gas-sensitive material according to any one of claims 1-4 in an ammonia sensor.
9. A method for preparing a room-temperature high-sensitivity reversible ammonia gas sensor, characterized in that, Includes the following steps: S1. Weigh an appropriate amount of any of the room temperature high-sensitivity reversible gas-sensitive material powders described in 1-4, add isopropanol, and grind until a uniform paste is formed. S2. Coat the paste-like material from S1 onto the surface of the substrate with gold electrodes, let it air dry to form a gas-sensitive thin film, and then weld it to the four corner bases to obtain the sensor device.